A Simple and Effective Synthesis of Benzolactones and Benzolactams by Noncatalytic Benzylic Oxidation of Cyclic Benzylic Ethers and N-Protected Cyclic Benzylic Amines with Sodium Chlorite as an Oxidant - Song, Ai-Ru; Yu, Jun; Zhang, Chi (Synthesis, 2012)
Sodium chlorite (NaClO2) was shown to be capable of oxidizing cyclic benzylic ethers and N-protected cyclic benzylic amines in a heterogeneous solvent system of 1,1,1-trichloroethane and water at 55–65 °C to give synthetically useful benzolactones and benzolactams, respectively, in high-to-excellent yields.
Keywords: lactones; lactams; amines; ethers; oxidations; heterocycles